OXYTOCIN MASSAGE FOR POST PARTUM MOTHERS - Ermiati, Ermiati; Salmaa, Qoori; Mutia, Indah; Parisa, Grisela; Aini, Ayyida; Fitria, Dini; Daiatul, Rifqii; Indriyanti, Deviana; Srimurni, Nita Ayu (Journal of Maternity Care and Reproductive Health, 2024)
Exclusive breastfeeding for 6 months is a beneficial activity for both mother and baby. However, smooth breastfeeding is often hampered, especially in the first days after giving birth. One of the causes is a lack of stimulation of the hormones prolactin and oxytocin which play a role in the smooth production of breast milk. Breast milk production can be accelerated with non-pharmacological measures, namely through oxytocin massage. This study aims to analyze the effect of oxytocin massage on the smooth flow of breast milk based on literature analysis. The method used is a literature review through searches from the PubMed, Science Direct and Google Scholar databases using various Indonesian and English keywords. Sorting articles uses inclusion and exclusion criteria and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines with 4 stages, namely identification, screening, eligibility, and acceptable results. The results of the search identified 907 articles, then they were screened and 507 articles were obtained, then at the feasibility stage 7 articles were obtained and it was decided that these 7 articles were acceptable. The results of the article review found that oxytocin massage provides comfort and relaxation to the mother and stimulates the release of oxytocin so that it can speed up the release of breast milk , while breast care will stimulate the production of lactifer (prolactin hormone) to accelerate breast milk production in postpartum mothers. In conclusion, the oxytocin massage method is effective in increasing breast milk production and facilitating milk production in post partum mothers. It is hoped that there will be further research regarding family involvement in the effectiveness of oxytocin massage intervention for post partum mothers.